Analysis of Thinking Ability Test Analysis of Economics Education Students in Accounting Lectures - Ihsan Ihsan; Abd. Muhyi Abidin; Hully Hully; Nguyễn Minh Anh (Gema Cendekia Institute, 2025)
This research uses a quantitative descriptive method, aiming to describe students' analytical thinking skills in completing accounting lecture assignments on business transaction analysis materials in general journals. The subjects of this study are 31 students of the Economics Education Study Program who have taken statistics courses. The instrument used to collect data in this study is in the form of a test in the form of a story question about the business transactions of a business entity which is prepared based on the criteria of analytical thinking skills that are spread for indicators of sorting, organizing, and attributing. The results showed that the average analytical thinking skills of students were well qualified, consisting of a sorting indicator of 3.64 (good), an organizational indicator of 3.31 (good), and an attribution indicator of 2.92 (good).